Modelo Prolab: MIA - Movimiento Inclusivo de Abastecimiento, solución logística para ollas comunes - Sánchez Arriola de Caballero, María Susana (2025)
This paper presents the proposal of the Inclusive Supply Movement (MIA), a logistics solution designed to address the problem of food insecurity in the common pots of Comas, Lima, thus contributing to sustainable development goals such as SDG 2: Zero Hunger and SDG 10: Reducing inequalities. Research reveals that 29% of the Peruvian population lives in monetary poverty, increasing the need for access to nutritious and affordable food. MIA seeks to provide a supply system that guarantees the daily delivery of fresh food inputs to these community organizations, optimizing costs and improving food quality. Validation was carried out through usability tests and surveys of the leaders of the common pots, achieving 97% delivery efficiency and an intention to adopt the service by 45% of the respondents. The financial impact of the project is expected to be significant, with a projected Net Present Value (NPV) of S/. 3'812,184.00 and an Internal Rate of Return (IRR) of 411%. Additionally, the social NPV is estimated at S/. 1'078,447.00 reflecting its contribution to community welfare. Socially, MIA contributes to reduce malnutrition, with a Social Relevance Index (SRI) of 50% linked to SDG 2 and reduces economic inequalities of beneficiary families, reaching an SRI of 66% related to SDG 10. This comprehensive approach not only addresses food deprivation, but also enhances community resilience and promotes local economic development.